Challenges to Global Implementation of Infrared Thermography Technology: Current Perspective - Michael Shterenshis (University Library System, University of Pittsburgh, 2017)
Medical infrared thermography (IT) produces an image of the infrared waves emitted by the human body as part of the thermoregulation process that can vary in intensity based on the health of the person. This review analyzes recent developments in the use of infrared thermography as a screening and diagnostic tool in clinical and nonclinical settings, and identifies possible future routes for improvement of the method. Currently, infrared thermography is not considered to be a fully reliable diagnostic method. If standard infrared protocol is established and a normative database is available, infrared thermography may become a reliable method for detecting inflammatory processes.